PERBANDINGAN EFEKTIVITAS PENGGUNAAN MEDIA AUDIOVISUAL DAN MEDIA LEAFLET TERHADAP PERILAKU CUCI TANGAN SISWA KELAS 6 SD DI SDN 3 CIHUNI KECAMATAN PAGEDANGAN KABUPATEN TANGERANG-BANTEN - Fathul Ulum; Yogie Erlangga Haq (Jurnal Kesehatan STIKes IMC Bintaro, 2019)
Hand washing with soap is an easy way and does not need expensive baiaya. Therefore, getting used to is teaching children and the whole family to live healthy from an early age. Thus, the lifestyle is clean and healthy. Our hands are one of the main pathways for the entry of germs into the body which are most often directly related to the mouth and nose. The purpose of this study was to determine the effectiveness of the use of audiovisual media and leaflet media on handwashing behavior of 6th grade elementary school students in SDN 3 Cihuni Tangerang Regency 2018. This research method is quantitative with the posttest only control group design non randomization design. The sample in this study was 60 respondents. This research was taken in total sampling. Data collection uses the WHO standard hand washing procedure hand check sheet. The results of this study were the values before the health education was carried out with the omission method, the leaflet method and the audiovisual method were in the "less good" category. Whereas after health counseling with the omission method is with the category of GOOD LESS = 75% with the number of students 15 and GOOD = 25% with the number of students 5 people, the total number of respondents is 20 students. With the leaflet method is the category of GOOD LESS = 30% with the number of students 6 and GOOD = 70% with the number of students 14 people, the total number of respondents is 20 students. And with the audiovisual method is the category of GOOD LESS = 15% with the number of students 3 and GOOD = 85% with the number of students 17 people, the total number of respondents is 20 students. This shows that the method of omission and leaflets is less effective while the audiovisual method is very effective. This study recommends health institutions, educational institutions to be able to maintain the cleanliness of their hands.